Kidney Rejection Following Simultaneous Liver-kidney Transplantation. Issue 7 (July 2020) - Shah, Sapna; Suddle, Abid; Callaghan, Christopher; Karydis, Nicholas; Shaw, Olivia; Horsfield, Catherine; Koffman, Geoff; Heaton, Nigel
Abstract : Background: Donor-specific antibodies are reported to increase the risk of rejection and reduce allograft survival following simultaneous liver-kidney transplantation. Optimal immunosuppression regimens to reduce this risk and to treat rejection episodes are underinvestigated. Methods: Cohort analysis of the first 27 simultaneous liver-kidney transplant recipients, between 2014 and 2018 at our unit, is performed under a new risk stratification policy. Those with donor-specific antibodies to class II HLA with a mean fluorescence intensity >10 000 are considered high risk for antibody-mediated rejection (AMR). These patients received immunosuppression, which consisted of induction therapy, tacrolimus, mycophenolate mofetil, and prednisolone. All other patients are considered low risk and received tacrolimus and prednisolone alone. Results: Three patients were high risk for rejection, and 2 of these patients developed AMR, which was treated with plasma exchange and intravenous immunoglobulin. At 1 y, their estimated glomerular filtration rate (eGFR) were 50 and 59 mL/min. Two other patients developed AMR, which was similarly treated, and their 1-y eGFR was 31 and 50 mL/min. The overall histologically proven acute rejection rate within the first year was 33%, and median eGFR, for the 27 patients, at 1 y was 52 mL/min and at 2 y was 49 mL/min. Conclusions: This study confirms that there is a risk of AMR following simultaneous liver-kidney transplantation despite increased immunosuppression. This can be effectively treated with plasma exchange and intravenous immunoglobulin.